2016
DOI: 10.14256/jce.1451.2015
|View full text |Cite
|
Sign up to set email alerts
|

Modul elastičnosti asfalta s bitumenom modificiranim gumenim granulatom kao vezivom

Abstract: Elastic modulus of asphalt with chemically stabilized rubber bitumenThe chemically stabilized rubber bitumen (CSRB) has been developed by researchers from the company MOL and the Pannonian University (Hungary). The CSRB is made of used automobile tyres, and it improves the quality of pavement, while also enabling an efficient use of used automobile tyres. Mechanical properties of the chemically stabilized crumb rubber bitumen are analysed in the paper. Although test results have shown that CSRB properties are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Therefore, the use of recycled polymer such as crumb rubber offers an inexpensive alternative [9]. For example, Kisgyörgy et al [10] concluded that adding rubber to asphalt binder improved the rutting and fatigue resistances of the asphalt mixture which extend the lifecycle and result in lower maintenance costs. Rubberized binders have improved asphalt pavement's quality, increased rutting and cracking resistance and eventually reduced maintenance costs [11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the use of recycled polymer such as crumb rubber offers an inexpensive alternative [9]. For example, Kisgyörgy et al [10] concluded that adding rubber to asphalt binder improved the rutting and fatigue resistances of the asphalt mixture which extend the lifecycle and result in lower maintenance costs. Rubberized binders have improved asphalt pavement's quality, increased rutting and cracking resistance and eventually reduced maintenance costs [11].…”
Section: Introductionmentioning
confidence: 99%
“…Not only polymers are used to modify asphalt binders and mixtures. Researchers also dealt with other additives, as indicated in the literature, including crumb rubber [5][6][7][8][9] produced as a result of waste tyre processing as well as natural asphalts [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…According to the Ordinance on management of waste tires [4], a tire is any product placed on the market as an independent product or as a component of another product. Waste tire recycling is also positive from the point of view of responsible waste management and environmental protection, precisely because of the fact that car tires are produced in large quantities and are considered a very problematic category of waste, as shown in [5,6]. Given that only 5 % of recycled tires are used for civil engineering purposes, the aim is to increase this percentage with new technologies and products that will enable adequate use of recycled tires [7].…”
Section: Introductionmentioning
confidence: 99%